Analysis of Code Writing Problem Solution Results in C Programming Course - Kyaw, Htoo Htoo Sandi; Kaneko, Keiichi; Funabiki, Nobuo (Proceedings of IEEE International Symposium on Consumer Electronics, 2024)
To advance the educational quality of C programming, we have proposed and implemented the C Programming Learning Assistant System (CPLAS) as a Web application system. CPLAS offers a Code Writing Problem (CWP) that requests students to write the source code from scratch to improve their code-writing skills. In past years, we have utilized code writing problems in our C programming courses. In this paper, we analyze the solution results of students taking the course in 2022. The results confirmed the effectiveness of the code validation function for the automatic marking and the coding rule checking function to improve readable code writing skills.